Biotope mapping in protected areas in the example of Belemedik Nature Park - Nuriye Say; Gamze Karadaş (Turkish Journal of Forestry)
In the processes of declaring protected areas and preparing management plans, biotope maps are a tool that provides important data on the cultural and natural structure of the area. Thanks to this feature, they are used as base data not only for protected areas but also in ecologically based spatial planning processes. This study aims to identify and map the biotopes of Belemedik Nature Park located at the foothills of the Toros Mountains in the Pozantı district of Adana province. In this context, the NUTS system was used as the basis for the coding of biotope types in order to create the classification system and standard area registration form of the CORINE Biotope Project. As a result of field observations and analyses, 13 sub-biotope types were defined in detail under 5 main biotope categories. The findings of the study show that forest biotopes play a dominant role in the ecological structure of the park, shrub and meadow areas provide significant contributions to biodiversity, and freshwater ecosystems are among the sensitive habitats that need to be protected. The created biotope map provides a solid foundation for planning and protection strategies that will contribute to the ecological and cultural sustainability goals of Belemedik Nature Park. As a result, suggestions were presented for the use of biotope maps as a planning material, for the preparation of management plans of the area, and for playing an active role in determining the principles of use of areas with recreation and tourism potential.